An inequity assessment framework for planning coastal and marine conservation and development interventions - Singh, Gerald G.; Keefer, Justine; Ota, Yoshitaka (Frontiers in Marine Science, 2023)
Sustainable development should promote equity with benefits for coastal communities.Many conservation and development initiatives promise to contribute to an equitable future without being designed to do so. Here, we promote an assessment tool to help interventions plan to promote equity through forecasting and evaluating the risks of contributing to inequities, in order to plan against them. Building from rich literatures of impact assessment, procedural justice, postcolonial studies, critical race theory, and fields in sociology studying the accrual of advantage and disadvantage among different groups, we propose the assessment framework follow key principles that center on understanding how interventions affect marginalized people, and assess how planning, implementation, and outcome decisions build on each other and reflect (or work against) broader systemic contextual pressures that perpetuate inequities. In forecasting and monitoring potential inequities, coastal communities and proponents of interventions should be able to plan against the realization of these adverse impacts.We show how the framework can be used in three case studies: 1) a climate adaptation project; 2) marine protected areas; 3) a debt relief program. Sustainable development is about promoting equity, but only with methods employed to confront and understand inequitable consequences can interventions do so.